I never thought of it that way [book club bag] : how to have fearlessly curious conversations in dangerously divided times - Guzmán, Mónica (Journalist) (BenBella Books, Inc., 2024)
"Partisanship is up, trust is down, and our social media feeds make us sure we're right and everyone else is ignorant (or worse). But avoiding one another is hurting our relationships and our society. Journalist Mónica Guzmán is the loving liberal daughter of Mexican immigrants who voted--twice--for Donald Trump. When the country could no longer see straight across the political divide, Mónica set out to find what was blinding us and discovered the most eye-opening tool we're not using: our own built-in curiosity. In this timely, personal guide, Mónica, the chief storyteller for the national cross-partisan depolarization organization Braver Angels, takes you to the real front lines of a crisis that threatens to grind America to a halt--broken conversations among confounded people. She shows you how to overcome the fear and certainty that surround us to finally do what only seems impossible: understand and even learn from people in your life whose whole worldview is different from or even opposed to yours. Drawing from cross-partisan conversations she's had, organized, or witnessed everywhere from the echo chambers on social media to the wheat fields in Oregon to raw, unfiltered fights with her own family on election night, Mónica shows how you can put your natural sense of wonder to work for you immediately, finding the answers you need by talking with people--rather than about them--and asking the questions you want, curiously. Whether you're left, right, center, or not a fan of labels: If you're ready to fight back against the confusion, heartbreak, and madness of our dangerously divided times--in your own life, at least--Mónica's got the tools and fresh, surprising insights to prove that seeing where people are coming from isn't just possible. It's easier than you think."--Publisher's description.